A nitrogen-doped carbon-coated copper-tungsten dual-site catalyst, a preparation method and application thereof
By constructing a Cu0-mixed valence WOx dual-site active center using a nitrogen-doped carbon-encapsulated copper-tungsten dual-site catalyst, the problem of selective hydroxylamine generation and condensation in existing technologies was solved, enabling efficient and green synthesis of cyclohexanone oxime and simplifying the process.
Patent Information
- Application Number
- CN202610342781.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-19
- Publication Date
- 2026-06-19
AI Technical Summary
Existing technologies struggle to selectively generate hydroxylamine intermediates and facilitate their condensation reaction with cyclohexanone, resulting in lengthy and hazardous steps in the traditional cyclohexanone-hydroxylamine route. Furthermore, existing copper-based catalysts exhibit low Faradaic efficiency, failing to meet the demands for efficient synthesis of cyclohexanone oximes.
A copper-tungsten dual-site catalyst encapsulated with nitrogen-doped carbon was used to prepare Cu0-mixed valence WOx (WO3/WO2) dual-site active centers via a hydrothermal method. The Cu0 site activated nitrate to initiate the reduction reaction, while the mixed valence WOx selectively adsorbed and stabilized hydroxylamine intermediates, promoting the adsorption and activation of cyclohexanone, thus realizing the electroreduction of nitrate and in-situ condensation of hydroxylamine.
This method enables highly selective synthesis of cyclohexanone oxime under mild conditions, simplifies the process, avoids the use of hazardous hydroxylamine salts, and improves yield and Faraday efficiency, aligning with the principles of green chemistry and sustainable development.
Smart Images

Figure CN122235762A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrocatalytic materials and green synthesis technology, specifically relating to a nitrogen-doped carbon-encapsulated copper-tungsten dual-site catalyst, its preparation method, and its application in the one-pot preparation of cyclohexanone oxime using nitrate and cyclohexanone as raw materials via a series electrocatalytic reaction. Background Technology
[0002] Cyclohexanone oxime is a key intermediate in the production of caprolactam and nylon-6. Its traditional industrial production commonly employs the "cyclohexanone-hydroxylamine (salt)" route. This process is not only lengthy but also requires the use of highly hazardous hydroxylamine salts (such as hydroxylamine sulfate) and produces large quantities of low-value ammonium sulfate as a byproduct, resulting in significant environmental pressure and economic costs. Therefore, developing a green, safe, and efficient new synthetic route for cyclohexanone oxime is of great significance.
[0003] In recent years, electrocatalytic synthesis technology has provided a new paradigm for the green manufacturing of chemical products due to its advantages such as the utilization of renewable electrical energy, mild reaction conditions, and high atom economy. Among these, nitrates (NO3) are a prime example. - As a cheap and abundant nitrogen source, the direct synthesis of high-value-added nitrogen-containing chemicals via electrocatalytic reduction has become a promising research direction. Theoretically, the electrocatalytic reduction of nitrates to hydroxylamine (NH2OH), followed by its in-situ condensation reaction with cyclohexanone to form cyclohexanone oxime, is an ideal atom-economical route that can perfectly replace traditional processes.
[0004] However, this tandem electrocatalytic process faces significant scientific challenges. First, the nitrate reduction reaction (NO3RR) is a complex process involving multiple electron-proton transfers, with products including nitrite, hydroxylamine, nitrogen, and ammonia. Selectively stopping the reaction at the hydroxylamine intermediate is extremely difficult because hydroxylamine is readily reduced to ammonia on the surface of most active catalysts. Currently, widely studied copper-based catalysts exhibit high activity for NO3RR, but their product selectivity typically favors the deep reduction of ammonia, resulting in generally low Faradaic efficiencies for hydroxylamine, which are insufficient to meet the requirements of subsequent condensation. Second, even if hydroxylamine is generated, the matching degree between its subsequent non-electrochemical condensation reaction rate with cyclohexanone and the electrochemical reduction step directly affects the efficiency of the entire tandem reaction. Therefore, developing a novel electrocatalyst capable of precisely controlling the reaction pathway, stabilizing the hydroxylamine intermediate, and promoting the condensation process is crucial for the practical application of this technology. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a nitrogen-doped carbon-encapsulated copper-tungsten dual-site catalyst, its preparation method, and its application in the one-pot preparation of cyclohexanone oxime via a series electrocatalytic reaction using nitrate and cyclohexanone as raw materials. As a cathode catalyst, it performs an electrocatalytic reaction in an electrolyte containing nitrate and cyclohexanone, generating cyclohexanone oxime in one step through a series process of "nitrate electroreduction-hydroxylamine in-situ condensation".
[0006] To achieve the above-mentioned technical objectives, the technical solution of the present invention is as follows: A method for preparing a nitrogen-doped carbon-encapsulated copper-tungsten dual-site catalyst includes the following steps: (1) According to the molar ratio of tungsten in tungstate to copper in copper salt of 1:1, add copper salt aqueous solution to tungstate aqueous solution, stir and mix thoroughly, and obtain copper tungstate (CuWO4) precursor through hydrothermal reaction; (2) Disperse the copper tungstate precursor in water by ultrasonication to obtain a copper tungstate aqueous solution. Add dopamine hydrochloride, stir evenly, and then add ammonia water to adjust the pH to alkaline. This allows dopamine hydrochloride to undergo oxidative self-polymerization on the surface of the copper tungstate precursor to form a polydopamine (PDA) coating layer, thus obtaining a CuWO4@PDA core-shell structure precursor. (3) Under a protective atmosphere, the CuWO4@PDA core-shell structure precursor was calcined at 700~800 °C to obtain a nitrogen-doped carbon-encapsulated copper-tungsten dual-site catalyst Cu / WO4. x @NC.
[0007] Preferably, in step (1), the tungstate is sodium tungstate or ammonium tungstate, and the copper salt is copper sulfate, copper chloride, copper acetate, or copper nitrate.
[0008] Preferably, in step (1), the temperature of the hydrothermal reaction is 150~180 ℃ and the time is 4~8 h.
[0009] Preferably, in step (2), the mass ratio of the copper tungstate precursor to dopamine hydrochloride is 8~15:1, and the pH is adjusted to 8~9 with ammonia.
[0010] Preferably, in step (3), the protective atmosphere is nitrogen, argon or helium, the heating rate is 2~10 ℃ / min, and the calcination time is 1~3 h.
[0011] The present invention also provides a nitrogen-doped carbon-encapsulated copper-tungsten dual-site catalyst prepared by the above preparation method.
[0012] In this invention, the nitrogen-doped carbon-encapsulated copper-tungsten dual-site catalyst uses nitrogen-doped carbon as the coating layer, and its active core consists of elemental copper (Cu). 0 Nanoparticles and tungsten oxide (WO3) xNanoparticles are tightly composited at the nanoscale, including tungsten oxide (WO3). x It contains two crystalline phases: tungsten trioxide (WO3) and tungsten dioxide (WO2).
[0013] This invention also provides the application of the above-mentioned nitrogen-doped carbon-encapsulated copper-tungsten dual-site catalyst for the electrocatalytic synthesis of cyclohexanone oxime; specifically, it is used as a cathode catalyst to carry out an electrocatalytic reaction in an electrolyte containing nitrate and cyclohexanone, generating cyclohexanone oxime in one step through a series of processes of "nitrate electroreduction-hydroxylamine in situ condensation".
[0014] The beneficial effects of this invention are: 1. This invention successfully constructed "Cu 0 - Mixed valence state WO x (WO3 / WO2) dual-site active center; wherein, Cu 0 The site efficiently activates nitrate to initiate the reduction reaction, while the closely adjacent mixed valence state WO x It can selectively adsorb and stabilize key hydroxylamine intermediates, effectively preventing their degradation in strongly reducing Cu. 0 Excessive reduction to ammonia at the site may simultaneously promote the adsorption and activation of cyclohexanone, thereby efficiently driving the tandem reaction and achieving one-pot synthesis of cyclohexanone oxime.
[0015] 2. The nitrogen-doped carbon-encapsulated copper-tungsten dual-site catalyst Cu / WO of the present invention x @NC exhibited significantly higher performance than single-metal comparison samples (Cu@NC or WO) in the one-step electrosynthesis of cyclohexanone oxime. x It exhibits excellent electrocatalytic performance with a high yield of @NC.
[0016] 3. This invention enables the direct and highly selective synthesis of cyclohexanone oxime from inexpensive nitrates and cyclohexanone under mild conditions, eliminating the need for the use and treatment of hazardous hydroxylamine salts. The process is greatly simplified, with high atom economy, and conforms to the concepts of green chemistry and sustainable development. Attached Figure Description
[0017] Figure 1 Cu / WO prepared in Example 1 x @NC-750, Cu / WO prepared in Comparative Example 1 x @NC-650, Cu / WO prepared in Comparative Example 2 x @NC-850, Cu@NC prepared in Comparative Example 3, and WO prepared in Comparative Example 4 x X-ray diffraction (XRD) pattern of @NC.
[0018] Figure 2 Cu / WO prepared in Example 1 xLinear voltammetric curves of electrocatalytic water dissociation, nitrate reduction and cyclohexanone oxime synthesis using @NC-750.
[0019] Figure 3 Cu / WO prepared in Example 1 x @NC-750, Cu / WO prepared in Comparative Example 1 x Cu / WO prepared by @NC-650 and Comparative Example 2 x Electrosynthesis performance of cyclohexanone oxime using @NC-850.
[0020] Figure 4 Cu / WO prepared in Example 1 x Comparison of the electrosynthesis performance of cyclohexanone oxime by Cu@NC-750 and Cu@NC prepared in Comparative Example 3.
[0021] Figure 5 Cu / WO prepared in Example 1 x @NC-750 and Comparative Example 4 were used to produce WO x Comparison of electrosynthetic performance of cyclohexanone oxime by @NC. Detailed Implementation
[0022] The technical solution of the present invention will be described below through specific embodiments, but the technical solution of the present invention is not limited to the specific embodiments.
[0023] Example 1
[0024] (1) Weigh 5 mmol sodium tungstate and 5 mmol copper sulfate pentahydrate, dissolve them separately in 40 mL deionized water, and slowly add the copper salt solution dropwise to the tungstate solution while stirring. Continue stirring for 30 minutes. Transfer the mixed solution to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor, place it in an oven, and react at 160 °C for 6 hours. After the reaction is complete, allow it to cool naturally, wash the resulting precipitate several times with deionized water and ethanol by centrifugation, and dry it overnight in a vacuum drying oven at 60 °C to obtain the copper tungstate (CuWO4) precursor; (2) Take 0.5 g of the above CuWO4 precursor, disperse it in 80 mL of deionized water, and sonicate it for 10 minutes to ensure uniform dispersion. Add 50 mg of dopamine hydrochloride and magnetically stir at 250 r / min for 15 minutes to ensure uniform mixing. Then, add ammonia water dropwise to adjust the pH of the solution to about 8.5, and continue stirring for 2 hours. After the reaction is complete, centrifuge to collect the solid product, wash it with deionized water, and dry it at 60 °C to obtain the polydopamine-coated core-shell structure precursor (CuWO4@PDA); (3) The above CuWO4@PDA precursor was placed in a tube furnace and heated to 750 °C at a heating rate of 5 °C / min under a nitrogen atmosphere, and held at this temperature for 2 hours. After pyrolysis, it was naturally cooled to room temperature, and the resulting catalyst was denoted as Cu / WO4. x @NC-750. (For example) Figure 1 As shown, XRD reveals the simultaneous presence of diffraction peaks for elemental Cu, WO3 (PDF#43-1096), and WO2 (PDF#32-1393), indicating the coexistence of the two phases WO3 and WO2.
[0025] Comparative Example 1 Same as Example 1, except that the calcination temperature in step (3) is 650 °C, and the resulting catalyst is denoted as Cu / WO. x @NC-650, such as Figure 1 As shown, XRD indicates that its main phases are elemental Cu (PDF#04-0836) and WO3 (PDF#43-1096).
[0026] Comparative Example 2 Same as Example 1, except that the calcination temperature in step (3) is 850 °C, and the resulting catalyst is denoted as Cu / WO. x @NC-850, such as Figure 1 As shown, XRD indicates that its main phases are elemental Cu and WO2, with only trace amounts of WO3.
[0027] Comparative Example 3 (1) Take 5 mmol of copper nitrate, dissolve it in deionized water, and add ammonia dropwise with stirring until precipitation is complete to obtain copper hydroxide precipitate. After washing and drying, calcine it in a muffle furnace at 400 °C for 2 hours to obtain copper oxide (CuO) precursor; (2) Take 0.5 g of the above CuO precursor, disperse it in 80 mL of deionized water, and sonicate it for 10 minutes to ensure uniform dispersion. Add 50 mg of dopamine hydrochloride and magnetically stir at 250 r / min for 15 minutes to ensure uniform mixing. Then, add ammonia water dropwise to adjust the pH of the solution to about 8.5, and continue stirring for 2 hours. After the reaction is complete, collect the solid product by centrifugation, wash it with deionized water, and dry it at 60 °C to obtain the polydopamine-coated core-shell structure precursor (CuO@PDA). (3) The above CuO@PDA precursor was placed in a tube furnace and heated to 750 °C at a heating rate of 5 °C / min under a nitrogen atmosphere, and held at this temperature for 2 hours. After pyrolysis, it was naturally cooled to room temperature, and the resulting catalyst was denoted as Cu@NC.
[0028] Comparative Example 4 (1) Take 5 mmol of ammonium tungstate, dissolve it in deionized water, adjust the pH to acidic with dilute hydrochloric acid to produce a precipitate. After washing and drying, calcine it in a muffle furnace at 500 °C for 2 hours to obtain tungsten trioxide (WO3) precursor; (2) Take 0.5 g of the above WO3 precursor, disperse it in 80 mL of deionized water, and sonicate it for 10 minutes to ensure uniform dispersion. Add 50 mg of dopamine hydrochloride and magnetically stir at 250 r / min for 15 minutes to ensure uniform mixing. Then, add ammonia water dropwise to adjust the pH of the solution to about 8.5, and continue stirring for 2 hours. After the reaction is complete, collect the solid product by centrifugation, wash it with deionized water, and dry it at 60 °C to obtain the polydopamine-coated core-shell structure precursor (WO3@PDA). (3) The above WO3@PDA precursor was placed in a tube furnace and heated to 750 °C at a heating rate of 5 °C / min under a nitrogen atmosphere, and held at this temperature for 2 hours. After pyrolysis, it was naturally cooled to room temperature, and the resulting catalyst was denoted as WO3@PDA. x @NC.
[0029] Performance testing of electrocatalytic synthesis of cyclohexanone oxime: 1. Specific test conditions: (1) Electrode preparation: Take 5 mg of catalyst, add 475 μL of anhydrous ethanol, 475 μL of deionized water and 50 μL of 5wt% Nafion solution, and sonicate for 30 minutes to form a uniform ink. Use a pipette to take 20 μL of this ink and coat it evenly on a 1 cm × 1 cm carbon paper. Let it air dry at room temperature to serve as the working electrode. The catalyst loading is approximately 0.1 mg / cm². -2 ; (2) Electrolysis system: An H-type electrolytic cell was used, with the prepared electrode as the working cathode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode. The electrolyte in the cathode chamber was 80 mL of 0.5 M potassium hydroxide solution containing 0.5 M KNO3 and 0.1 M cyclohexanone. The electrolyte in the anode chamber was 80 mL of 0.5 M potassium hydroxide solution containing 0.5 M KNO3. The two chambers were separated by a Nafion 117 membrane.
[0030] (3) Electrochemical Testing: Before all electrochemical tests, the electrolyte was purged with high-purity argon gas (Ar, 99.999%) until saturation to remove dissolved oxygen. Cyclic voltammetry (CV) was used at 100 mV s⁻¹. -1 The catalyst electrode was activated by approximately 50 scans at a scan rate ranging from 0.2 V to -1.3 V vs. RHE potential. The linear voltammetry (LSV) test was performed at a scan rate of 5 mV s. -1Samples were collected in 0.5 M KOH solution, 0.5 M KOH solution containing 0.5 M KNO3, and 0.5 M KOH solution containing 0.5 M KNO3 and 0.1 M cyclohexanone, respectively. Potential-constant electrolysis was performed using the chronoamperometry method. A constant reduction potential (-0.9 V vs. RHE) was applied to the cathode on an electrochemical workstation, and electrolysis was carried out for 2 hours, while the current-time curves were recorded simultaneously.
[0031] (4) Product Analysis: After electrolysis, the electrolyte in the cathode chamber was analyzed. The product was analyzed by nuclear magnetic resonance (NMR) hydrogen spectroscopy. 1 The amount of cyclohexanone oxime (CYCO) produced was quantitatively analyzed by ¹H NMR; ammonium ions (NH₄⁺) were determined by indophenol blue spectrophotometry. + The concentration of nitrite (NO2) was determined using the Grignard reagent method. - )concentration.
[0032] 2. The specific test results are as follows: (1) The Cu / WO4 ratio was preliminarily analyzed using linear voltammetry curves. x Electrocatalytic activity of the @NC-750 catalyst in the hydrogen evolution reaction (HER), nitrate reduction reaction (NO3RR), and cyclohexanone oxime electrosynthesis (ESCYCO). For example... Figure 2 As shown, when KNO3 is added to the electrolyte, the current density at the same potential is significantly increased compared to the pure KOH system, and the initial reduction reaction potential shifts significantly to the positive side. This indicates that in a solution containing nitrate, the Cu / WO3 ratio... x @NC-750 exhibits good NO3RR catalytic activity. Furthermore, the addition of cyclohexanone improves the Cu / WO3 ratio. x The NC-750 catalyst still maintains a high current density, indicating that the addition of cyclohexanone has no significant interference with its NO3RR activity.
[0033] (2) A series of Cu / WO3 samples calcined at different temperatures under a potential of -0.9 V vs. RHE x Performance testing was conducted on the @NC catalyst. Figure 3 It can be seen that the Cu / WO sample calcined at 750 ℃ x @NC-750 exhibited the best electrosynthetic performance of cyclohexanone oxime, with a CYCO yield of 39.43 mg h. -1 cm -2 And Cu / WO x @NC-650 and Cu / WO x The CYCO yield of @NC-850 was 29.05 mg h. -1 cm -2 and 32.86 mg h -1 cm -2 .
[0034] (3) Cu / WO at different potentials x @NC-750 and catalyst Cu@NC, WO x @NC performs performance comparisons, from Figure 4 and Figure 5 It can be seen that Cu / WO x @NC-750 exhibits significantly better electrosynthetic yields of CYCO than Cu@NC and WO at the same potential. x @NC.
Claims
1. A method for preparing a nitrogen-doped carbon-encapsulated copper-tungsten dual-site catalyst, characterized in that, Includes the following steps: (1) According to the molar ratio of tungsten in tungstate to copper in copper salt of 1:1, add copper salt aqueous solution to tungstate aqueous solution, stir and mix thoroughly, and obtain copper tungstate precursor by hydrothermal reaction; (2) Disperse the copper tungstate precursor in water by ultrasonication to obtain a copper tungstate aqueous solution. Add dopamine hydrochloride, stir evenly, and then add ammonia water to adjust the pH to alkaline. This allows dopamine hydrochloride to undergo oxidative self-polymerization on the surface of the copper tungstate precursor to form a polydopamine coating layer, thus obtaining the CuWO4@PDA core-shell structure precursor. (3) Under a protective atmosphere, the CuWO4@PDA core-shell structure precursor was calcined at 700~800 °C to obtain a nitrogen-doped carbon-encapsulated copper-tungsten dual-site catalyst Cu / WO4. x @NC.
2. The preparation method according to claim 1, characterized in that, In step (1), the tungstate is sodium tungstate or ammonium tungstate, and the copper salt is copper sulfate, copper chloride, copper acetate or copper nitrate.
3. The preparation method according to claim 1, characterized in that, In step (1), the temperature of the hydrothermal reaction is 150~180 ℃ and the time is 4~8 h.
4. The preparation method according to claim 1, characterized in that, In step (2), the mass ratio of the copper tungstate precursor to dopamine hydrochloride is 8~15:1, and the pH is adjusted to 8~9 with ammonia.
5. The preparation method according to claim 1, characterized in that, In step (3), the protective atmosphere is nitrogen, argon or helium, the heating rate is 2~10 ℃ / min, and the calcination time is 1~3 h.
6. A nitrogen-doped carbon-encapsulated copper-tungsten dual-site catalyst prepared by the preparation method according to any one of claims 1-5.
7. The application of the nitrogen-doped carbon-encapsulated copper-tungsten dual-site catalyst according to claim 6, characterized in that, It was used for the electrocatalytic synthesis of cyclohexanone oxime; Specifically, it is used as a cathode catalyst to carry out an electrocatalytic reaction in an electrolyte containing nitrate and cyclohexanone, generating cyclohexanone oxime in one step through a series of processes of "nitrate electroreduction-hydroxylamine in situ condensation".